pH Switchable Nanoplatform for In Vivo Persistent Luminescence Imaging and Precise Photothermal Therapy of Bacterial Infection - Yan, Li‐Xia; Chen, Li‐Jian; Zhao, Xu; Yan, Xiu‐Ping (Advanced functional materials, 2020)
Photothermal therapy (PTT) is one of the most promising approaches to combat multidrug‐resistant bacteria with less potential to induce resistance and systemic toxicity. However, uncontrollable distribution of photothermal agents leads to lethal temperatures for normal cells, and failure to offer timely and effective antibacterial stewardship. A pH switchable nanoplatform for persistent luminescence imaging‐guided precise PTT to selectively destroy only pathological cells while protecting nearby normal cells in bacterial infected microenvironment is shown. The PLNP@PANI‐GCS is fabricated by grafting polyaniline (PANI) and glycol chitosan (GCS) onto the surface of persistent luminescence nanoparticles (PLNPs). It takes advantage of the long persistent luminescence of PLNPs to realize autofluorescence‐free imaging, the pH‐dependent light–heat conversion property of PANI to get a stronger photothermal effect at pH 6.5 than pH 7.4, and the pH environment responsive surface charge transition of GCS. Consequently, PLNP@PANI‐GCS enables effective response to bacterial‐infected acid region and electrostatic bonding to bacteria in vivo, ensuring the spatial accuracy of near‐infrared light irradiation and specific heating directly to bacteria. In vivo imaging‐guided PTT to bacterial infection abscess shows effective treatment. PLNP@PANI‐GCS has great potential in treating multidrug‐resistant bacterial infection with low possibility of developing microbial drug resistance and little harm to normal cells. A pH switchable nanoplatform is developed for in vivo persistent luminescent imaging and precise photothermal therapy of bacterial infections. This nanoplatform exhibits specific photothermal therapy to acidic bacterial‐infected regions but no damage to normal tissues.